Network Brokerage: An Integrative Review and Future Research Agenda - Kwon, Seok-Woo; Rondi, Emanuela; Levin, Daniel Z.; De Massis, Alfredo; Brass, Daniel J. (Journal of Management, 2020)
Network brokerage research has grown rapidly in recent decades, spanning the boundaries of multiple social science disciplines as well as diverse research areas within management. Accordingly, we take stock of the literature on network brokerage and provide guidance on ways to move this burgeoning research area forward. We provide a comprehensive review of this literature, including crucial dimensions of the concept itself in terms of brokerage structure and behavior, a set of key categories of factors surrounding the brokerage concept (antecedents, outcomes, and moderators), and an overview of brokerage dynamics over time. We use these dimensions and categories to depict network brokerage’s theoretical and empirical underpinnings as well as evaluate prior research efforts. In so doing, we offer a means to summarize and synthesize this large, interdisciplinary literature, identify important research gaps, and offer promising directions for future research.